Screening of castor germplasm for wilt reaction and morpho-molecular characterization of resistant genotypes. Issue 3 (March 2023) - Rajput, Dhavalsinh; Patel, M.P.; Kumar, Sushil; Patel, Rumit; Katba, Pankaj
Abstract: Castor ( Ricinus communis L.) is an important industrial versatile non-edible oilseed C3 crop belongs to spurge family. Its oil has exceptional properties which provides an industrial importance to this crop. The present investigation was aimed to evaluate the genotypes of castor for Fusarium wilt reaction in pot followed by characterization of resistant genotypes for yield related traits in field and inter-genotype genetic diversity at DNA level. The percent disease incidence (PDI) among 50 genotypes ranged from 0 to 100%. A total of 36 genotypes were found wilt resistant (28 highly resistant and 8 resistant). ANOVA revealed that the genotypes MSS was significant for each trait studied, indicating the existence of plentiful variability in the experimental material. The morphological characterization showed that DCS-109 (73.30 cm) had a dwarf stature The genotype RG-1954 was superior for oil content (50.29%) with moderate for shelling out (67.63). RG-1673 was outstanding for seed boldness as 100 seed weight for this genotype was maximum (38.98 gm). JI-403 had maximum seed yield per plant (SYPP; 354.88 gm). SYPP positively associated with all traits except oil and seed length:breadth ratio. The path analysis revealed that the direct effects of NPR (0.549), TLFP (0.916), and CPP on SYPP are quite significant. A total of 38 alleles from 18 SSR markers were amplified in 36 genotypes. The NJ tree could divide 36 genotypes into three main clusters. AMOVA revealed 15% and 85% variance among and within subpopulations, respectively. Both morphological and SSR data demonstrated to be effective tools for discerning inter-genotypes diversity and categorizing high-yielding and disesae-tolerant castor genotypes lines.